Teacher's Translanguaging Practice in EFL Classroom Interaction in A Junior High School - Pakpahan, Cindy Luasen (Universitas Negeri Medan, 2025)
This research intends to examine the teacher’s translanguaging practices in EFL classroom interaction at a junior high school setting. A qualitative research approach was adopted. The data gathered through observation and interviews. The participant in this study was a seventh-grade English teacher from SMP Negeri 5 Percut Sei Tuan. The findings revealed that the teacher utilized four types of translanguaging practices: (1) translanguaging within one named language (Indonesian), (2) translanguaging through translation, (3) translanguaging through peer support, and (4) translanguaging through two named languages (Indonesian and English). These practices were employed to deliver instructions, clarify learning materials, and ensure students’ understanding. The reasons for using translanguaging included students’ limited vocabulary mastery, the need to clarify teacher instructions and the creation of a comfortable learning environment. The study concludes that translanguaging is an effective pedagogical strategy for enhancing student comprehension and supporting the teaching-learning process of English as a foreign language.